1984
DOI: 10.1042/bj2180459
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glucose on the activity of phosphofructokinase in the mucosa of rat small intestine

Abstract: In common with other phosphofructokinase isoenzymes, phosphofructokinase in the epithelial cells of rat small-intestinal mucosa is activated by fructose 2,6-bisphosphate. However, fructose 2,6-bisphosphate was found not to be present in mucosa as judged by three criteria: (1) chromatography on Sephadex G-25 of crude mucosal extracts from fed rats did not result in a decrease, or indeed any change, in the activity of phosphofructokinase under suboptimal conditions at pH7; (2) ultrafiltrates of mucosal extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
1

Year Published

1985
1985
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…Subsequently, Louis et al (1985) reported that fructose 2,6-bisphosphate was present in isolated enterocytes at concentrations comparable to those observed for liver (Hue, 1982;Pilkis et al, 1983). In this letter we report that fructose 2,6-bisphosphate is in fact present in mucosa under the conditions used by Jamal et al (1984), but that its concentration is one order of magnitude less than under those used by Louis et al (1985). The difference reflects differences in intestinal preparation and also in the composition of the commercial diets with which the rats were fed.…”
supporting
confidence: 49%
See 3 more Smart Citations
“…Subsequently, Louis et al (1985) reported that fructose 2,6-bisphosphate was present in isolated enterocytes at concentrations comparable to those observed for liver (Hue, 1982;Pilkis et al, 1983). In this letter we report that fructose 2,6-bisphosphate is in fact present in mucosa under the conditions used by Jamal et al (1984), but that its concentration is one order of magnitude less than under those used by Louis et al (1985). The difference reflects differences in intestinal preparation and also in the composition of the commercial diets with which the rats were fed.…”
supporting
confidence: 49%
“…This value is 2.4-fold less than for whole intestine and 9.7-fold less than for enterocytes from rats fed solely on the Bantin & Kingman diet. We therefore conclude that the concentration of fructose 2,6-bisphosphate in intestine under the conditions used by Jamal et al (1984) was an order of magnitude less than under the conditions used by Louis et al (1985). Different types of intestinal preparation, when used in conjunction with different brands of commercial chow diet, can result in very different rates of glucose metabolism and fructose 2,6-bisphosphate concentration.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…for at least six cell preparations. fructose 2,6-bisphosphate nor 6-phosphofructo-2-kinase were detected in intestinal mucosa (Jamal et al, 1984). However, mucosal phosphofructokinase, like that of other tissues (Hers et al, 1982), was stimulated by fructose 2,6-bisphosphate (Jamal et al, 1984).…”
Section: Walter Stocklein and Hanns-ludwig Schmidtmentioning
confidence: 90%